Assessment of intracranial vessels in association with carotid atherosclerosis and brain vascular lesions in rheumatoid arthritis - Csaba Oláh; Zsófia Kardos; Mariann Sepsi; Attila Sas; László Kostyál; Harjit Pal Bhattoa; Katalin Hodosi; György Kerekes; László Tamási; Attila Valikovics; Dániel Bereczki; Zoltán Szekanecz (Arthritis Research & Therapy, 2017)
Abstract Background Stroke has been associated with rheumatoid arthritis (RA). We assessed patients with RA and healthy control subjects by transcranial Doppler (TCD), carotid ultrasonography and brain magnetic resonance imaging (MRI). Methods Altogether, 41 female patients with RA undergoing methotrexate (MTX) or biologic treatment and 60 age-matched control subjects underwent TCD assessment of the middle cerebral artery (MCA) and basilar artery. Pulsatility index (PI), resistivity (resistance) index (RI) and circulatory reserve capacity (CRC) were determined at rest (r) and after apnoea (a) and hyperventilation (h). The presence of carotid plaques and carotid intima-media thickness (cIMT) were also determined. Intracerebral vascular lesions were investigated by brain MRI. Results MCA PI and RI values at rest and after apnoea were significantly increased in the total and MTX-treated RA populations vs control subjects. MCA CRC was also impaired, and basilar artery PI was higher in RA. More patients with RA had carotid plaques and increased cIMT. Linear regression analysis revealed that left PI(r) and RI(r) correlated with disease duration and that left PI(r), RI(r), PI(a), PI(h) and basilar PI correlated with disease activity. Right CRC inversely correlated with 28-joint Disease Activity Score. Disease activity was an independent determinant of left PI(a) and right CRC. Compared with long-term MTX treatment alone, the use of biologics in combination with MTX was associated with less impaired cerebral circulation. Impaired cerebral circulation was also associated with measures of carotid atherosclerosis. Conclusions To our knowledge, this is the first study to show increased distal MCA and basilar artery occlusion in RA as determined by TCD. Patients with RA also had CRC defects. We also confirmed increased carotid plaque formation and increased cIMT. Biologics may beneficially influence some parameters in the intracranial vessels.